2019
DOI: 10.3389/fphys.2019.00520
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Activity of Ryanodine Receptors Contributes to Calcium Mishandling in Cardiomyocytes of Metabolic Syndrome Rats

Abstract: Metabolic syndrome (MetS) has become a global epidemic. MetS is a serious health problem because of its related cardiovascular complications, which include hypertension and delayed heart rate recovery after exercise. The molecular bases of cardiac dysfunction in MetS are still under scrutiny and may be related to anomalies in the activity and expression of key proteins involved in the cardiac excitation–contraction coupling (ECC). The cardiac Ca 2+ channel/ryanodine receptor (RyR2) parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 62 publications
4
18
0
Order By: Relevance
“…With respect to ER Ca 2+ regulatory machineries, cardiac up-regulation of IP3R3 and IP3R2 receptors, down-regulation of SERCA2a, and decreased RyR2 activity (T2814 phosphorylation) caused by HF feeding were noted in HF diet–fed mouse hearts and are responsible for feeding Ca 2+ from the ER to mitochondria, resequestration of Ca 2+ into ER, and releasing Ca 2+ from ER/sarcoplasmic reticulum stores, respectively ( 32 ). Consistent with our present findings, earlier work demonstrated decreased cardiac SERCA levels and RyR2 Ca 2+ release as well as elevated hepatic IP3R1 and IP3R2 in metabolic diseases including diet-induced obesity ( 33 , 34 ). The disparity in IP3Rs subtypes may be related to tissue specificity.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to ER Ca 2+ regulatory machineries, cardiac up-regulation of IP3R3 and IP3R2 receptors, down-regulation of SERCA2a, and decreased RyR2 activity (T2814 phosphorylation) caused by HF feeding were noted in HF diet–fed mouse hearts and are responsible for feeding Ca 2+ from the ER to mitochondria, resequestration of Ca 2+ into ER, and releasing Ca 2+ from ER/sarcoplasmic reticulum stores, respectively ( 32 ). Consistent with our present findings, earlier work demonstrated decreased cardiac SERCA levels and RyR2 Ca 2+ release as well as elevated hepatic IP3R1 and IP3R2 in metabolic diseases including diet-induced obesity ( 33 , 34 ). The disparity in IP3Rs subtypes may be related to tissue specificity.…”
Section: Discussionsupporting
confidence: 93%
“…Those results are in agreement with our model of sucrose supplementation in drinking water, in which the rats became obese with an increased epididymal fat and body weight (Table 1) [25]. The weight gain in our model [25] contrasts with other studies using the same animal model in which no weight differences [45][46][47] or much lower weight increases were found [48]. Regardless of the variability in the characteristics developed, sucrose-induced MetS has been a frequently studied model to elucidate molecular alterations of this condition [45][46][47][48][49], and the sucrose-drinking protocol used in our study induced central characteristics of MetS, such as obesity, hyperinsulinemia, hypertriglyceridemia, and insulin resistance ( Table 1 and Fig 1).…”
Section: Mets Ratssupporting
confidence: 91%
“…About the sucrose delivery mode, Singh et al [43] reported that male Sprague Dawley rats fed with high sucrose diet (55% of energy as sucrose) supplied by pellets for 15 weeks, did not develop obesity, hypertriglyceridemia or insulin resistance, unlike reported in other studies [44], however, by supplying sucrose in the drinking water (32% sucrose), rats developed obesity and insulin resistance in 8 to 10 weeks [43]. Those results are in agreement with our model of sucrose supplementation in drinking water, in which the rats became obese with an increased epididymal fat and body weight (Table 1) [25]. The weight gain in our model [25] contrasts with other studies using the same animal model in which no weight differences [45][46][47] or much lower weight increases were found [48].…”
Section: Mets Ratssupporting
confidence: 91%
See 1 more Smart Citation
“…All the results were expressed as mmol/l. On p189, TG/HDL was assessed, as previously described in [49,50].…”
Section: Methodsmentioning
confidence: 99%